Power of Regenerative Braking with Kinetic Energy Recovery System - Ramadhan, Mochamad Edoward; Guntur, Harus Laksana (Institut Teknologi Sepuluh Nopember, 2014)
Braking and acceleration is often carried out by the driver on the highway with heavy traffic intensity. This leads to a lack of effective implementation of the Kinetic Energy Recovery System (KERS) on urban vehicles, because of the relatively short time braking and discontinued. Research results show that the braking process resulted in a 15-20% loss of energy of the fuel energy combustion engine. To restore the energy loss due to braking, kinetic energy recovery methods developed in excess of a vehicle are often called Kinetic Energy Recovery System (KERS). In this research, experimental study of the influence of variations in speed changes just before braking on the characteristics of KERS. To realize this experimental study, conducted engineering process simple mechanism incorporating KERS braking system comprising, 1.82kg mass flywheel and generator 12volt voltage, 800watt maximum power. Experiment begins with analyzing the flywheel kinetic energy generated by setting VSD (Variable Speed Drive) 10hz, 15hz, 20hz and 25hz, then at each end of the round setting made braking. The next experiment is done by finding the speed variation characteristics of KERS just before braking, braking then performed to determine the change of electrical energy that can be raised KERS. This paper result efficiency power of regenerative braking with kinetic energy recovery system in laboratory scale. Based on observations made on 50Ah 12 volt battery charging, electrical mechanical KERS apparently capable of producing an average 14.07volt, the average current 5.078ampere and average power electrical energy 71.3watt. The result show charging capacity is still small round duration at 3015.5rpm 6.88second produce 95mAh and efficiency of KERS at 1197rpm 119%, 1816rpm 75%, 2229rpm 60% and 2766rpm 53%.